Physiological markers of endurance capacity and Yo-yo Intermittent Recovery test performance in professional soccer players considering their playing position - Estrella, R.; Ferreira, R.; Silvino, V.; Vilhena, L.; Silva, M.; Santos, M.; Vieira, R.; Prado, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Endurance capacity is a critical component of performance in soccer, characterized by intermittent high-intensity activities interspersed with periods of low-intensity recovery. The Yo-Yo Intermittent Recovery Test (YYIR1) has emerged as a popular and reliable tool for assessing aerobic capacity and endurance in soccer players. This study aims to verify the association between the physiological markers of endurance capacity and YYIR1 performance in professional soccer players taking into consideration the playing position. METHODS: Twenty-six professional soccer athletes (defenders n = 10, midfielders n = 10, forwards n = 6) performed the YYIR1 and underwent a cardiopulmonary exercise test in order to assess their ventilatory thresholds (anaerobic threshold, respiratory compensation point and maximal oxygen consumption). RESULTS: No differences were observed in the parameters at anaerobic threshold among playing positions. However, defenders reached the respiratory compensation point at a higher speed compared to midfielders (15.00 ± 1.33 vs 13.20 ± 1.48, respectively). Moreover, we found a positive correlation between VO2 max and YYIR1 total distance (r = 0.492; p = 0.02) considering all participants. CONCLUSION: Our results highlight the interplay between maximal oxygen consumption and YYIR1 performance. We observed that VO2 max work load is the best predictor of YYIR1 performance compared to the submaximal thresholds. Additionally, defenders exhibited a higher speed at the respiratory compensation point compared to midfielders. These findings suggest differences in cardiorespiratory adaptations associated with different playing positions in soccer, which can inform training regimens and performance optimization strategies to specific positions.